Setting the Effectiveness of Law Position and Code Notary to the Quality of Performance - M. Indah Verena Ferdiyanti; Dwi Fahri Hidayatullah; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This study aims to determine the readiness of governments to regulate and promote the performance of the notary through UUJN and implementation supervision performed by the Supervisory Council, how effective arrangements and Notary Code UUJN to the quality of performance of a notary. The writing method is based on the normative juridical research with a normative approach carried out by analyzing the material by reference to the norms of law - legal norms in the implementation of the code of conduct notary. The results of this study that the notary in carrying out its duties and responsibilities can not be separated from the code of conduct that has been set. But not infrequently the notary work outside their code of ethics. Actions that violate the code of conduct notary, such as signing a deed that is not done in the presence of a notary, a deed outside the office and a deed which is not in accordance with the provisions contained in Law No. 2 of 2014. This of course led to the violation of the law regarding the conduct of their duties. So supervision by the Indonesian Notary Association (INI) has an important role towards the creation of a notary who work according to the code of conduct. Monitoring carried out INI is more enforcement against notary abuse, such as giving reprimand, warning and suspension or even expulsion from membership. So supervision by the Indonesian Notary Association (INI) has an important role towards the creation of a notary who work according to the code of conduct. Monitoring carried out THIS is more enforcement against notary abuse, such as giving reprimand, warning and suspension or even expulsion from membership. So supervision by the Indonesian Notary Association (INI) has an important role towards the creation of a notary who work according to the code of conduct. Monitoring carried out THIS is more enforcement against notary abuse, such as giving reprimand, warning and suspension or even expulsion from membership.Keywords: Notary Act (UUJN); Notary Code; Indonesian Notaries Association.